The Peaceful Settlement of Conflicts according to Islamic Jurisprudence and International Law: Review of ‘Islamic Law and International Law: Peaceful Resolution of Disputes’ by Emilia Justyna Powell, Oxford University Press, 2020. - Zuhrah, Fatimah (Jurnal Syariah dan Hukum Komparatif, 2025)
This review examines Islamic Law and International Law: Peaceful Resolution of Disputes (Oxford University Press, 2020) by Emilia Justyna Powell, a groundbreaking interdisciplinary study that explores how Islamic legal traditions influence the engagement of Muslim-majority states with international dispute resolution mechanisms. Drawing from original empirical data and classical Islamic jurisprudence, Powell argues that domestic legal structures—whether secular, Islamic, or hybrid—significantly shape states' preferences for international conflict resolution methods. The book highlights both the consonance and dissonance between Islamic law and international law, particularly in the context of peaceful settlement. Powell challenges prevailing assumptions of uniformity among Islamic Law States and demonstrates the importance of legal pluralism in international relations. Through critical analysis, this review assesses the strengths of Powell’s approach—her empirical rigor, legal-philosophical insight, and contribution to debates on global justice—while also noting the limitations, including the need for a more nuanced understanding of hybrid legal systems and broader geopolitical factors. Overall, the book is a significant scholarly contribution that bridges comparative law, Islamic studies, and international legal theory, offering valuable insights into the evolving dynamics of legal identity and interstate conflict management.